2000
DOI: 10.1074/jbc.m003147200
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Entry Mediated by Store Depletion,S-Nitrosylation, and TRP3 Channels

Abstract: The mechanism for coupling between Ca 2؉ stores and store-operated channels (SOCs) is an important but unresolved question. SOC-mediated Ca 2؉ entry is complex and may reflect more than one type of channel and coupling mechanism. To assess such possible divergence the function and coupling of SOCs was compared with two other distinct yet related Ca 2؉ entry mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 42 publications
(86 reference statements)
3
106
2
Order By: Relevance
“…donate (data not shown), consistent with observations using HEK-293 cells [32]. Several other non-voltage-activated Ca 2+ entry pathways that are distinct from SOC are also not inhibited by 2-APB, including maitotoxin-evoked Ca 2+ entry in hepatocytes [17], S-nitrosylation-induced influx in a smooth muscle cell line [33], Ca 2+ influx caused by diacylglycerol analogues in PC12 cells [34], muscarinic activation of non-selective cation channels in smooth muscle [35]. In many instances, 2-APB can be used to block SOC-mediated Ca 2+ influx, although it should be noted that it is not completely specific for SOC [10].…”
Section: Discussionsupporting
confidence: 76%
“…donate (data not shown), consistent with observations using HEK-293 cells [32]. Several other non-voltage-activated Ca 2+ entry pathways that are distinct from SOC are also not inhibited by 2-APB, including maitotoxin-evoked Ca 2+ entry in hepatocytes [17], S-nitrosylation-induced influx in a smooth muscle cell line [33], Ca 2+ influx caused by diacylglycerol analogues in PC12 cells [34], muscarinic activation of non-selective cation channels in smooth muscle [35]. In many instances, 2-APB can be used to block SOC-mediated Ca 2+ influx, although it should be noted that it is not completely specific for SOC [10].…”
Section: Discussionsupporting
confidence: 76%
“…In numerous cells, application of the phosphatase inhibitor CalyA induces condensation of the actin cytoskeleton at the PM (15,17,44,45). CalyA enhances association of ezrin, radixin, and moesin proteins, powerful mediators of actin cross-linking, with the PM (54,55).…”
Section: A Secretion-like Coupling Mechanism In Corneal Endothelialmentioning
confidence: 99%
“…2-APB was first described as a non-competitive antagonist of the IP3 receptor. 100,101 Many later studies showed that inhibitory effect of 2-APB on Ca 2+ signaling was primarily due to its ability to block SOCE. [101][102][103] This was taken as evidence for the then prevailing conformational coupling model that postulated a role for IP3 receptors in the activation of CRAC channels.…”
Section: -Aminoethyldiphenyl Borate (2-apb)mentioning
confidence: 99%